The Description of Bullying in High School Students - Tri Nurhidayati; Muhammad Fatkhul Mubin; Kholid Al Faizin (Media Keperawatan Indonesia, 2019)
The bullying is the desire to hurt others. This has been shown in actions that cause a person to suffer. Someone who has stronger power has done this to others who are weaker. Bullying people usually do this with feeling happy. The purpose of this study was to determine the description of bullying in high school students. The design that has been used in this study is quantitative research, with a cross-sectional approach. Bullying has been measured using the MDP questionnaire. This study has measured the bullying of 118 students of class XI MIPA of SMAN I Tengaran, which was obtained through purposive random sampling. Data has been analyzed univariately. The results of the study have shown that high school students have experienced bullying. bullying has been done to high school students while at school. more high school students have received weak intensity bullying. High school students have received mild bullying by an average of 93.2 and bullying has an average weight of 6.8. The description of bullying is experienced by high-intensity high school students.